Investigation of the Energy Efficiency of Electrohydrodynamic Drying under High Humidity Conditions - Yuki Taoka; Shota Ai; Radon Dhelika; Shigeki Saito (Journal of Engineering)
Electrohydrodynamic (EHD) drying is an emerging drying technology that is based primarily on the phenomenon of ionic discharge between two electrodes. The aim of this study was to experimentally investigate the energy efficiency of the EHD drying based on the corona discharge current. Moreover, we aimed to compare the energy efficiency of the EHD drying with that of other available drying technology options under the condition of high humidity, which mimics Indonesia’s environment as a potential target for implementation, given that it is of interest to investigate the feasibility of the EHD drying in a real environment. The results show that the dominant parameters of the EHD drying rate are the corona discharge current and the moisture content zones of the target objects. Findings from this study show that the EHD drying technology could be effectively used to replace the conventional drying process in developing countries having high humidity environments and facing energy consumption challenges.